Morphological and mechanical study of microfiber bundle - Li, Jiande. (2009)
A tendon is a fibrous band of collagenous tissue that is primarily used to transfer the force created by the muscle to the bone, thus allowing possible joint movement. When the tendon becomes impaired, tissue engineering uses tissue scaffold that serves as matrix for tissue growth, to restore and reconstruct the function of impaired tissues.